What is the value of biotic seed dispersal in post‐fire forest regeneration? - José Benedicto‐Royuela; José Miguel Costa; Ruben Heleno; Joaquim S. Silva; Helena Freitas; Pedro Lopes; Sara Beatriz Mendes; Sérgio Timóteo (Conservation Letters, 2024)
Abstract World forests face many threats, including wildfires, with tremendous ecological, social, and economic implications. Mediterranean ecosystems have evolved in the presence of fire, but changes to fire regimes associated with other global changes pose new challenges to postfire community regeneration. Forest regeneration largely depends on plant adaptations to survive wildfires or on the recolonization of burnt areas through seed dispersal. However, the value of the service provided by wild animals to postfire forest regeneration remains unevaluated. Here, we estimate the economic value of the biotic seed dispersal service in postfire restoration in Portugal. We combine budgeted costs of governmental Emergency Stabilisation Reports with network analysis that estimates the dependency of the Portuguese flora on biotic seed dispersal and on alternative fire regeneration strategies. Replacing the services provided by seed dispersers during postfire regeneration of Portuguese forests would cost 23,061,621€/year, highlighting the need for integrative policies that promote resilient forests.